Pengembangan Aplikasi Web Game Edukasi Matematika Berbasis Node.js dan RESTful API untuk Meningkatkan Minat Belajar - Nadya Devi Febita; Arsito Ari Kuncoro; Eko Siswanto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
To address the challenge of low interest exhibited by elementary school students in their mathematics learning, this investigation presents the development of an interactive, web-based educational game that integrates gamification principles. The construction and rollout of the application were executed using the Waterfall system development life cycle, leveraging Node.js and Express.js, and were architected around a RESTful API to ensure future scalability and optimal system performance.. An evaluation of the system's functionality was undertaken utilizing Black Box Testing, a process that verified the intended operation of all features and confirmed the absence of significant malfunctions. User validation was subsequently carried out by administering questionnaires to a group of sixth-grade students at SD Negeri Sendangguwo 01. The accumulated results from this assessment revealed a feasibility score reaching 92.27%, which is situated within the